Dynamic and Acoustic Characterisation of Automotive Wheels - Francesca Curà; Graziano Curti (Shock and Vibration)
The subject of this paper is the dynamic and acoustic characterisation of an automotive wheel. In particular, an experimental research activity previously performed by the authors about the dynamic behaviour of automotive wheels has been extended to the acoustic field.